Answer:
a) 4(9
+2)
b)6(7
+1)
Explanation:
a) Prove that for any positive integer n, 4 evenly divides 32n-1
checking whether the statement is correct or not
∴ n = 1;
=
![3^(2n) -1](https://img.qammunity.org/2021/formulas/mathematics/college/4ps3ft85aibw9jnoop591f3rcllm92cs16.png)
=
![3^(2*1) -1](https://img.qammunity.org/2021/formulas/mathematics/college/l2kf9qk1p9pjbmgts532t90t0zj8v09yyf.png)
= 9 - 1
= 8
hence it is divisible by 4
Let the statement is for n = k
∴
= 4
(equation 1)
= 4
![x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p9sq9b3rc5nwoqzhzc8wcaj51b36281l9g.png)
= 4
(equation 1)
Now, we have to proof the statement is true for n = k+1
=
![3^(2(k+1)) -1](https://img.qammunity.org/2021/formulas/mathematics/college/uasmdtf1ameqhbpt118iciud0tfyno4vr4.png)
=
(
)
Adding & Subtracting 8
=
![(3^(2k) * 3^(2) ) -1 +8 -8](https://img.qammunity.org/2021/formulas/mathematics/college/nkrss6s6ud4p4sdistlh8r6zlxh07uhvn5.png)
=
![9^(k) * 9 -9 + 8](https://img.qammunity.org/2021/formulas/mathematics/college/7ntotxq5wf3hcejwpi6lkfve0hdr6x0x81.png)
taking common 9
= 9(
-1)+8
= 9 (4
) +8 (from equation 1)
= 36
+ 8
= 4(9
+2)
if (9
+2) = p
then = 4p
Since
= 4p evenly divisible by 4
therefore given statement is true
b)Prove that for any positive integer n, 6 evenly divides
![7^(n) - 1](https://img.qammunity.org/2021/formulas/mathematics/college/6k6gu4nfa9qf7d7ovj6uyssbgwxibjr9w6.png)
checking whether the statement is correct or not
∴ n = 1;
![7^(n) - 1](https://img.qammunity.org/2021/formulas/mathematics/college/6k6gu4nfa9qf7d7ovj6uyssbgwxibjr9w6.png)
7 - 1
6
6 is divisible by 6
hence the given statement is true for n = 1
let it also true for n = k
(equation 2)
Now we have to proof the statement is true for n = k+1
![7^(k+1) - 1](https://img.qammunity.org/2021/formulas/mathematics/college/lwjnbrh9jm9ggjv78314lgyoseu37cojvw.png)
![7^(k)*7 - 1](https://img.qammunity.org/2021/formulas/mathematics/college/vmdjer1kq6ofsg5qi625coddf6edkrkexd.png)
Adding & Subtracting 6
![7^(k)*7 - 1 +6 - 6](https://img.qammunity.org/2021/formulas/mathematics/college/16kv7iec7zc3w3f2m6i9qpl60vs1srwyyv.png)
![7^(k)*7 - 7 +6](https://img.qammunity.org/2021/formulas/mathematics/college/q8ahp78agdr6be1wdy1tulso6cc766djjp.png)
![7(7^(k)* - 1) +6](https://img.qammunity.org/2021/formulas/mathematics/college/utr31ieoqtune0rslhe8ztvuxo9dzlhwm9.png)
7(6
)+6 ( from equation 2)
= 42
+ 6
= 6(7
+1)
if 6(7
+1) = p
then = 6p
Since
= 6p evenly divisible by 6
therefore given statement is true